2020
DOI: 10.1371/journal.pcbi.1007748
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the roles of firing rates and spike bursts in shaping the STN-GPe beta band oscillations

Abstract: The excess of 15-30 Hz (β-band) oscillations in the basal ganglia is one of the key signatures of Parkinson's disease (PD). The STN-GPe network is integral to generation and modulation of β band oscillations in basal ganglia. However, the role of changes in the firing rates and spike bursting of STN and GPe neurons in shaping these oscillations has remained unclear. In order to uncouple their effects, we studied the dynamics of STN-GPe network using numerical simulations. In particular, we used a neuron model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 99 publications
(196 reference statements)
2
16
0
Order By: Relevance
“…However, a more recent study indicates that this abnormal neural dynamic is critically dependent on GPe rather than on cortex and STN (de la Crompe et al, 2020 ). In line with the above hypothesis, another new study has shown that the bursting of STN depends on the bursting of GPe neurons (Bahuguna et al, 2020 ). Taken together, we believe that the GPe-STN network is important in the maintenance and propagation of β synchronization.…”
Section: Main Textmentioning
confidence: 70%
See 1 more Smart Citation
“…However, a more recent study indicates that this abnormal neural dynamic is critically dependent on GPe rather than on cortex and STN (de la Crompe et al, 2020 ). In line with the above hypothesis, another new study has shown that the bursting of STN depends on the bursting of GPe neurons (Bahuguna et al, 2020 ). Taken together, we believe that the GPe-STN network is important in the maintenance and propagation of β synchronization.…”
Section: Main Textmentioning
confidence: 70%
“…Usually, β oscillation is not exaggerated until several days after 6-OHDA lesion (Mallet et al, 2008b ), suggesting it needs a long-term adaptive change of the synaptic alteration. There are many hypotheses concerning the generation and propagation of abnormal β oscillation activity in PD (Walters et al, 2007 ; Shouno et al, 2017 ; Bahuguna et al, 2020 ). Several studies have suggested that the intrinsic β oscillation in the GPe-STN network is too weak to act as a pacemaker and the β oscillation might be generated by cortex, and later amplified by the GPe-STN network (Brittain and Brown, 2014 ; Koelman and Lowery, 2019 ).…”
Section: Main Textmentioning
confidence: 99%
“…However, we speculate that besides the STN-GPe, the backprojections from GPe to striatum together with recurrent connections within the GPe can form an effective excitatory-inhibitory network necessary for generating oscillations. It is worth noting that previous experimental data (Mallet et al, 2006;de la Crompe et al, 2020;Sharott et al, 2017) and computational models (Kumar et al, 2011;Mirzaei et al, 2017;Bahuguna et al, 2020) provide a strong evidence that strengthening of D2-SPN→GPe-TI connection is also sufficient to induce βband oscillations/synchrony in the ongoing activity state of the BG. Thus, here, we provide a unified explanation of impaired transient response and ongoing activity in PD state.…”
Section: Discussionmentioning
confidence: 85%
“…While β-band oscillations are a clear neural signature of PD, the mechanisms underlying the emergence of these oscillations are still not understood. Both experimental data (Plenz and Kital, 1999;Hammond et al, 2007;Tachibana et al, 2011;de la Crompe et al, 2020) and computational models (Kumar et al, 2008;Tachibana et al, 2011;Holgado et al, 2010;Pavlides et al, 2015;Bahuguna et al, 2020) have implicated essentially all the various network interactions in generating oscillations. Here we have developed the BG model primarily to understand the transient response and found that the same model can also generate β-band oscillations.…”
Section: Effect Of Striato-pallaidal and Pallido-subthalamic Pathwaysmentioning
confidence: 99%
“…However, reproducing the temporal patterning of beta oscillations has received little attention. It was reported very recently that spike bursting in a small proportion of neurons in the feedback loop formed by the STN and the globus pallidus pars externa (GPe) could contribute to transient beta oscillations [20]. Models of the STN-GPe feedback loop have been shown to generate Introducing average burst duration profiles.…”
Section: Introductionmentioning
confidence: 99%